Intelligent system stability using type-2 fuzzy controller - D., Nagarajan; J., Kavikumar; M., Lathamaheswari; S., Broumi (Penerbit UTHM, 2019)
To avoid mathematical complexity, Interval T2FSs (IT2FSs) have been pertained in majority of the fields. Type-2 fuzzy sets (T2FSs) handle a greater modeling and uncertainties that exist in the real world applications especially in control systems. One of the important components that influence the fuzzy controller is the triangular norm, which is the aggregation operator. For getting the stability of a control system T-norm operator can be preferred. Gaussian Interval Type-2 Membership Function (GIT2MF) has been used in this research. Mathematical properties of aggregation operator also proved using Gaussian Interval Type-2 Weighted Arithmetic (GIT2WA) operator. The aim of this research is analyzing the stability of an inverted pendulum using Interval Type-2 Fuzzy Logic Controller (IT2FLC) and the results are compared with traditional Proportional Integrated Derivative (PID) controller. It is observed that IT2FL controller gives better stability under imprecise condition.